ATIM-29. A PHASE 1 STUDY OF PF-06840003, AN ORAL INDOLE 2, 3-DIOXYGENASE 1 (IDO1) INHIBITOR IN PATIENTS WITH MALIGNANT GLIOMAS. (6th November 2017) - Reardon, David; Desjardins, Annick; Rixe, Olivier; Cloughesy, Timothy; Alekar, Shilpa; Gamelin, Erick; Williams, Jason; Meissen, John; Taylor, Carrie; Lassman, Andrew
Abstract: BACKGROUND: PF-06840003 is a highly selective and active IDO1 inhibitor, presumed to cross the blood brain barrier. IDO1, produced by cancer or immune cells, by affecting tryptophan catabolism, producing immunosuppressive metabolites such as kynurenine, inhibits proliferation of T cells, induces T cell anergy and apoptosis and promotes generation and activity of regulatory T cells and MDSCs. IDO1 is involved in malignant glioma immunosuppression, playing a key role in acquired resistance to PD-1/PD-L1 or CTLA-4 inhibition; their combination with IDO1 inhibition can lead to more efficacious antitumor immunity. Preclinical studies show high PF-06840003 CNS penetration and in the GL261 murine glioma model a synergistic effect in combination with PD-1/PD-L1 blockade, CTLA-4 inhibition, radiation therapy and temozolomide. This ongoing multi-center clinical trial aims to assess the safety, PK and PD activity of PF-06840003 in malignant glioma, confirm CNS penetration and verify its effectiveness in combination. METHODS: Escalation phase primary objectives evaluate safety and tolerability of increasing dose levels of daily PF-06840003 and determine the maximum tolerated dose and recommended phase 2 dose. Secondary objectives evaluate single and multiple dose plasma PK, CSF PK, dose and concentration response relationship for target engagement and PD biomarkers, and anti-tumor activity using MacDonald and immune Response Assessment for Neuro-Oncology (iRANO) criteria. Exploratory objectives evaluate urine PK, CSF PD biomarkers, cytokine, chemokine transcripts, gene signatures and T-cell repertoire, and anti-tumor activity (iRANO). Sequential cohorts receive pre-specified PF-06840003: 125 mg, 250 mg once daily; 250 mg, 500 mg, 750 mg, and 1000 mg twice daily. Dose escalation follows a modified Toxicity Probability Interval method, targeting a DLT rate of 27.5% and an acceptable DLT interval 22.5 to 32.5%. Positive preliminary PK-PD data (500mg cohort), safety data and CNS penetration justifies this late breaking abstract. Date of planned analysis August 2017. RESULTS/CONCLUSION: Will appear in final LBA. [ClinicalTrials.gov: NCT02764151]